Analysis of The Effect of Teacher Competency and Work Environment on Teacher Performance With Motivation as Intervening Variable at Private Vocational School in Bondowoso District - Arif Wahyudi; Nurul Qomariah; Abadi Sanosra (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2022)
This research is motivated by several gaps or differences in research results with expert opinions, also supported by data from the evaluation of the performance of private vocational school teachers in Bondowoso showing that the achievement of teacher performance indicators is not optimal up to 100%, even tends to be far from the target it should be. This is to determine directly or indirectly the effect of teacher competence and work environment on teacher performance through work motivation as an intervening variable for private vocational school teachers in Bondowoso Regency. The total population of this study was 331 employees, while the number of samples was 181 using proportional sampling technique. The analysis technique used is the Structural Equation Model (SEM) using WarpPLS 5.0. The results of data analysis show that teacher competence and work environment have a significant effect on work motivation of 0.002 and 0.001, teacher competence, work environment and work motivation have a significant effect on teacher performance of 0.009 and 0.001, teacher competence and work environment have a significant effect on teacher performance through job satisfaction as an intervening variable is 0.001.